Transformation of Communal Identity in Slovenia: The Dolenjska Region from the 6th till the 21st Century - Rebolj, Anja (TESTINSTANZ: Wissenschaftliche Schriften der Universität Münster, 2019)
The core question addressed in this study is how the political regimes have modified the social structure of communities in the region of Dolenjska, of Podgorje in particular, in southeast Slovenia in the course of fifteen centuries. By means of ethnographic and historical data and by mobilising social-anthropological models of social structure, of social relationships, value and exchange, and of the reproduction of the social order as part of cosmological one, the analysis of the various ways in which the vicissitudes that have marked Slovenia’s political history – the focus being on the 19th and 20th centuries – has shown how community structures have adapted themselves so as to persist in the face of profound political change. Die Kernfrage dieser Arbeit ist, wie die politischen Regimes die soziale Struktur der Gemeinschaften in der Region Dolenjska, insbesondere von Podgorje, im Südosten Sloweniens im Laufe von fünfzehn Jahrhunderten verändert haben. Anhand ethnographischer und historischer Daten und unter Bezugnahme auf sozialanthropologische Modelle der Sozialstruktur, sozialen Beziehungen, Wert und Austausch sowie der Reproduktion der Sozialordnung als Teil der Kosmologie, hat die Analyse der unterschiedlichen Ansätze durch welche die Wirren, die die politische Geschichte Sloweniens geprägt haben – mit dem Fokus auf das 19. und 20. Jahrhundert – gezeigt, wie sich die Gemeinschaftsstrukturen angepasst haben, um angesichts der tiefgreifenden politischen Veränderungen bestehen bleiben zu können. Permalinkhttps://nbn-resolving.de/urn:nbn:de:hbz:6-85199584038 ISBN978-3-8405-0202-6 Paperback, I, 373 Seiten